PENGARUH PENAMBAHAN MULTI NUTRIENT SAUCE PADA RANSUM TERHADAP PERTAMBAHAN BOBOT BADAN HARIAN SAPI POTONG - Sodikin, Ali; ,, Erwanto; Adhianto, Kusuma (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
Effect of Multi Nutrients Sauce (MNS) in ration of beef cattle on average daily gain (ADG) was studied on November 10th, 2015 up to December 09th, 2015 at Pulung Kencana village, Tulang Bawang Tengah, Subdistrict, Provinsi Tulang Bawang Barat. The experimental design used was complete randomized block design with three treatments P0 (basal diet), P1 (basal diet + 10% MNS), and P2 (Unila diet + 10% MNS). Result of this research indicated that ADG of beef cattle for P0, P1, P2 was 1,28 kg/head/day; 1,56 kg/head/day; 1,26 kg/head/day, respectively. Average of ration consumption based on dry matter were 9,08 kg/head/day; 9,24 kg/head/day; 9,11 kg/head/day, respectively. Efficiency of ration were 0,1403±0,0180 kg weight/kg ration; 0,1687±0,0234 kg weight/kg ration; 0,1385±0,0271 kg weight/kg ration, respectively. Income over feed cost (IOFC) were 2,76 ; 3,24 ; 3,18, respectively. It could be concluded that addition of 10% MNS in ration of beef cattle didn’t affect (P>0,05) on ADG, ration consumption, efficiency of ration, and IOFC. Keywords : Beef Cattle, Multi Nutrient Sauce, Average Daily Gain, Efficiency of Ration, Income Over Feed Cost